Evaluación de la proporción del abono de soca de maíz (zea mays l.) En la calidad físico-química del suelo en los Amarillos, Tosagua - Loor Ganchozo, Lucia Isabel (2021)
Currently, conventional agriculture based on inappropriate practices, causes negative effects on the quality of the soil and its properties, which has repercussions on the human's health and the environment. Based on the above, the objective of this research is to evaluate the proportion of corn (Zea mays L.) waste fertilizer in the improvement of the physical-chemical quality of the soil, in Los Amarillos community, Tosagua canton, Manabi province. For its effect, the physical-chemical conditions of the soil were diagnosed, carrying out the recognition of the study area through a mapping of the area, with which it was possible to show that hard corn is grown at a scale of 60% compared to other crops; in addition, it is determined that the corn waste is not reused. The evaluated parameters were: porosity, texture, color, organic matter, pH, P, K, Fe, Ca/K ratio, Mg/K and Ca + Mg/K; obtaining as initial results high values in the parameters of: pH (7.8), potassium (38 ppm) and the Ca/Mg ratio (5.2 meq/100ml). By applying the fertilizer, it was possible to determine that, the greater the amount of it, the greater the significant difference between the treatments; especially, the T4 of 5 kg of fertilizer is undermined from corn, which presented notable improvements in the conditions of: pH (7.2), organic matter (25.87 %), P (239.33 ppm), K ( 7.98 meq/100ml), Fe (45.33 ppm), Ca/K ratio (1.71 meq/100ml), Mg/K (0.38 meq/100ml) and Ca + Mg / K (2.1 meq/100ml); followed by T3, which was the one that presented the greatest variation in the conditions of color (8.59) and porosity (59.67).